Predicting working women purchasing behaviour of Malaysian halal cosmetic products by using Theory of Planned Behaviour - Kaur, Kamaljeet; Osman, Syuhaily; Mustapha, Siti Maziha (Academic Research Publishers, 2014)
This paper focuses on the Malaysian Working Women purchasing behaviour of Malaysian made halal cosmetic products. A self-administered questionnaire was designed as an instrument to gather information. The Theory of Planned Behaviour was used to measure the purchasing behavior. Three independent variables namely attitude, subjective norm and perceive behavioral control was used to determine purchasing behavior. A survey was conducted and 425 working women in the Klang Valley responded to the questionnaire. Results from the multiple regression showed that all the independent predictors are significant and subjective norm being the most important predictor. This study will provide the Malaysian halal cosmetic industry in particular with a greater understanding of the consumer behavior relating to halal cosmetics specially amongst working women. Lastly, recommendations and implications of finding have been discussed based on the findings.